I segreti degli strumenti di scrittura Storia, design, materiali, produzione - Titone, Alessandro (bu,press, 2013)
The world of writing instruments contains a surprising wealth of information. These objects constitute an integral part of the industrial design culture and are of great technical and anthropological interest. The tools presented here are some of the most common and widely used in our daily lives. Through the study of these objects, this volume examines and collects comparable information that can be found in any other industrial product.